Exploring the resisting factor of ict in education among teachers: A case study in UAE - Alnajjar, Saba Hikmat Abbood; El Metwally, Amani Ali; Abu Bakar, Azizi; Abdullah, Mohd Syukri Yeoh; Ridzwan, Zahrom; Syed Idrus, Syed Zulkarnain (Science and Engineering Research Support Society, 2019)
While considerable attention is being paid to reforming education systems to prepare students for the challenges of globalization and a knowledge-based economy, teacher education models in the Asia Pacific remain insufficiently critiqued. There is an urgent need to rethink teacher education as, in spite of decades of investment and development, major problems of inequality, attrition, incomplete and inadequate learning continue to blight our education systems. It is proposed that teacher education needs to become more culturally authentic as teaching and learning are best viewed as culturally scripted activities. The utilization of indigenous knowledge will be central to this task. The article concludes with some suggestions for how the task may be started.